IMPLEMENTASI CHALLENGE RESPONSE AUTHENTICATION MECHANISM (CRAM) UNTUK KEAMANAN TRANSAKSI PERANGKAT IoT - Hendro FJ Lami; Hendro F J Lami; Stephanie I Pella (Universitas Nusa Cendana, 2021)
This research aims to secure data transaction in Internet of Things (IoT)devices using the challenge-response authentication mechanism (CRAM). The research choose uses ESP 8266 and ESP 32 to develop the system for their ability to run micropython programming language. Using a random challenge to grant authentication protects the system from replay attack from intruders. In each authentication process, the client receives a 10 digit random number to be encrypted using a shared key and sent back to the server. The server then checks if the client posses the correct key by decrypting the encrypted challenge using the same shared key. Access is granted if the decryption result is equal to the original challenge.